Archiving Archaeological Data: Understanding current practice through case studies from established repositories - Tim Evans; Hella Hollander; Ulf Jakobsson; Valentijn Gilissen; Holly Wright (Internet Archaeology)
The article describes and compares key policies and workflows from three long standing digital repositories for archaeological data: Data Archiving and Networked Services (DANS) of the Netherlands, the Swedish National Data Service (SND), and the Archaeology Data Service (ADS) from the United Kingdom. The workflows examined are representative of operational workflows around data assessment and data removal that are common to all data repositories, as well as specific strategies for dealing with Microsoft Access databases, a commonly deposited file format used by archaeologists for assessment and analysis.